2019
DOI: 10.3389/fpsyg.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Occupational Demands and Well-Being of Performing Artists: A Systematic Review

Abstract: Background: Performing artists are exposed to a range of occupational demands from organisational, interpersonal and intrapersonal sources, which may impact their well-being. The aim of this systematic review was to evaluate and synthesise the literature where researchers have considered the relationship between occupational demands and well-being in performing artists. Methods: A mixed-methods systematic review was conducted including professional and student performing arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 124 publications
(245 reference statements)
3
24
0
1
Order By: Relevance
“…The new-found ‘me time’ and ability to prioritize healthier lifestyles is also of note, providing insight into how future professional lives can be optimized. This fits well with the finding by Willis et al (2019) that music-making, performance activities, and social support were identified by performing artists as important for better wellbeing, and finding new ways to enable and support these, while also reinstating job security and income, will be important for the sector moving forward. Further research should focus on a wider demographic and take a longitudinal approach in order to understand how these initial effects change, or not, as the course of the pandemic continues.…”
Section: Studysupporting
confidence: 89%
See 2 more Smart Citations
“…The new-found ‘me time’ and ability to prioritize healthier lifestyles is also of note, providing insight into how future professional lives can be optimized. This fits well with the finding by Willis et al (2019) that music-making, performance activities, and social support were identified by performing artists as important for better wellbeing, and finding new ways to enable and support these, while also reinstating job security and income, will be important for the sector moving forward. Further research should focus on a wider demographic and take a longitudinal approach in order to understand how these initial effects change, or not, as the course of the pandemic continues.…”
Section: Studysupporting
confidence: 89%
“…Among the challenges, many – such as canceled work, unexpected loss of income, challenges of working from home, and feelings of loss and grief – were linked to the immediate effects of the pandemic. Others – such as the precariousness of freelance working and mental health problems – were also challenges pre-COVID ( Bartleet et al, 2019 ; Willis et al, 2019 ) and appeared to be exacerbated by the impact of the lockdown. As the pandemic progresses, performing arts professionals continue to face closed venues, canceled work, and the restrictions of social distancing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, unlike most European countries, the majority (over 85%) of orchestral musicians are not salaried, but self-employed as members of freelance orchestras, on short-term contracts as extra or deputy players, or on an ad hoc basis (Teague and Smith, 2015; Association of British Orchestras (ABO), 2019; Willis et al, 2019). These freelance musicians build busy portfolio careers comprising a rich and varied combination of performing activities, such as orchestral and chamber music, West End shows, community work, commercial and recording sessions, and also teaching (Bartleet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These freelance musicians build busy portfolio careers comprising a rich and varied combination of performing activities, such as orchestral and chamber music, West End shows, community work, commercial and recording sessions, and also teaching (Bartleet et al, 2019). Maintaining a successful portfolio career as a freelance musician requires a broad skill-set, including effective problem-solving skills, good communication, teamwork, adaptability, and small business and entrepreneurial skills, in addition to excellent performing ability (Bennett and Hennekam, 2018;Willis et al, 2019). Although there are studies showing that self-employment is associated with higher job and life satisfaction than fixed employment by one or more organizations (Warr, 2018), studies of freelance classical musicians have found that work and financial insecurity are associated with increased anxiety (Dobson, 2010;Oakland et al, 2012).…”
Section: Introductionmentioning
confidence: 99%